Methodology of Introducing Fleet Management System - Rogić, Kristijan; Šutić, Branislav; Kolarić, Goran (Promet - Traffic&Transportation, 2008)
Fleet management systems are increasingly changing invarious transport companies. Although according to claims ofdifferent producers, the usage of such systems can achieve greatsavings in the business operation, the studies show that for optimalfunctioning of such systems it is necessary to carry out theevaluation of the company and the very systems according toseveral criteria. The methodology that allows the FM implementationwithin the transport companies starts from the analysisof the characteristics of carriers, characteristics ofprogramme packages, which is followed by the evaluation accordingto several criteria which influence the final choice. Theobjective of such approach is the adaptation to the users' requirementswhich eventually results in the improvement andsavings in the operation.